Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
nj+k = p
Step-by-step explanation:
n = (p-k)/j
Multiply each side by j
nj = (p-k)/j *j
nj = p-k
Add k to each side
nj +k = p-k+k
nj+k = p
N = (p-k)/j // - (p-k)/j
N-((p-k)/j) = 0
(-1*(p-k))/j+N = 0
So it’s 0. Hope this helps!
(-1*(p-k))/j+(N*j)/j = 0
N*j-1*(p-k) = 0
N*j+k-p = 0
(N*j+k-p)/j = 0
(N*j+k-p)/j = 0 // * j
N*j+k-p = 0
N-((p-k)/j) = 0
(-1*(p-k))/j+N = 0
So it’s 0. Hope this helps!
(-1*(p-k))/j+(N*j)/j = 0
N*j-1*(p-k) = 0
N*j+k-p = 0
(N*j+k-p)/j = 0
(N*j+k-p)/j = 0 // * j
N*j+k-p = 0
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.